MIV-150 and zinc acetate combination provides potent and broad activity against HIV-1 - Mizenina, Olga (2017)
We previously showed that the combination of the non-nucleoside reverse transcriptase inhibitor (NNRTI) MIV-150 with zinc acetate (ZA) formulated in a carrageenan (CG; MZC) gel provided macaques significant protection against vaginal simian-human immunodeficiency virus-RT (SHIV-RT) challenge, better than either MIV-150/CG or ZA/CG. The MZC gel was shown to be safe in a phase 1 clinical trial. Herein, we used in vitro approaches to study the antiviral properties of ZA and the MIV-150/ZA combination, compared to other NNRTIs. Like other NNRTIs, MIV-150 has EC50 values in the subnanomolar to nanomolar range against wild type and NNRTI or RT-resistant HIVs. While less potent than NNRTIs, ZA was shown to be active in primary cells against laboratory-adapted and primary HIV-1 isolates and HIV-1 isolates/clones with NNRTI and RT resistance mutations, with EC50 values between 20 and 110 μM. The MIV-150/ZA combination had a potent and broad antiviral activity in primary cells. In vitro resistance selection studies revealed that previously described NNRTI-resistant mutations were selected by MIV-150. ZA-resistant virus retained susceptibility to MIV-150 (and other RTIs) and MIV-150-selected virus remained sensitive to ZA. Notably, resistant virus was not selected when cultured in the presence of both ZA and MIV-150. This underscores the potency and breadth of the MIV-150/ZA combination, supporting preclinical macaque studies and the advancement of MZC microbicides into clinical testing.